Bone Union of Osseous Microvascular Free Tissue Transfer in Mandibular Reconstruction. Issue 1 (January 2022) - Tamaki, Akina; Sethuraman, Shruthi; Shi, Lucy; Zhao, Songzhu; Carver, Keith C.; Hatef, Angel; Luttrull, Michael; Seim, Nolan B.; Kang, Stephen Y.; Ozer, Enver; Agrawal, Amit; Old, Matthew O.
Objectives: Osseous microvascular free tissue transfer (MFTT) is the gold standard for reconstruction for most segmental mandibulectomy defects. The most common osseous MFTT utilized in reconstruction is the fibular, scapular, and osteocutaneous radial forearm (OCRF) free flap. We evaluated postoperative bone union as well as clinical complications following MFTT and the impact of various patient and reconstructive characteristics, including type of osseous MFTT. Study Design: Retrospective cohort study. Setting: Tertiary care academic hospital. Methods: This study examined patients who underwent osseous MFTT for mandibular defects from January 2017 to January 2019. Results: An overall 144 osteotomies in 58 patients were evaluated. Of the 144 junctions, 28 (19.4%) showed radiographic nonunion. Patients who underwent preoperative (odds ratio [OR] = 0.30, P = .027) and postoperative (OR = 0.28, P = .003) radiation had a significantly lower bone union score. Time from surgery to postoperative imaging was associated with higher bone union scores (OR = 1.07, P = .024). When bone union scores were compared among types of MFTT, fibular (OR = 5.62, P = .008) and scapular (OR = 4.69, P = .043) MFTT had significantly higher scores than OCRF MFTT. Twelve (20.7%) patients had postoperative complications. There was no statistically significant correlation between clinical complications and various variables, including type of osseous MFTT. Conclusion: Pre- and postoperative radiation and time from surgery have an impact on bone union. Regarding the type of MFTT, fibular and scapular MFTT appeared to have higher bone union when compared with OCRF. There was no impact of bone union or type of osseous MFTT on clinical complications.